Bibliometric Analysis of Funding Aspect in the Domain of Marine Protected Area - Roby Fadillah; Yonvitner; Luky Adrianto; Hefni Effendi (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2025)
This paper conducts a comprehensive literature review on the aspect of funding in the management of Marine Protected Areas (MPAs) using bibliometric analysis through the VOSviewer software. Indonesia, as a country with high biodiversity, heavily relies on marine ecosystems, making effective MPA management reliant on adequate funding for monitoring, surveillance, and habitat rehabilitation. International publication data were collected from Scopus (2000-2024) using the keywords